Biodegradable polymeric microsphere-based drug delivery for inductive browning of fat - Jiang, Chunhui; Kuang, Liangju; Merkel, Madeline P.; Yue, Feng; Cano-Vega, Mario A.; Narayanan, Naagarajan; Kuang, Shihuan; Deng, Meng (Frontiers in Endocrinology, 2015)
Brown and beige adipocytes are potent therapeutic agents to increase energy expenditure and reduce risks of obesity and its affiliated metabolic symptoms. One strategy to increase beige adipocyte content is through inhibition of the evolutionarily conserved Notch signaling pathway. However, systemic delivery of Notch inhibitors is associated with off-target effects and multiple dosages of application further faces technical and translational challenges. Here, we report the development of a biodegradable polymeric microsphere-based drug delivery system for sustained, local release of a Notch inhibitor, DBZ. The microsphere-based delivery system was fabricated and optimized using an emulsion/solvent evaporation technique to encapsulate DBZ into poly(lactide-co-glycolide) (PLGA), a commonly used biodegradable polymer for controlled drug release. Release studies revealed the ability of PLGA microspheres to release DBZ in a sustained manner. Co-culture of white adipocytes with and without DBZ-loaded PLGA microspheres demonstrated that the released DBZ retained its bioactivity, and effectively inhibited Notch and promoted browning of white adipocytes. Injection of these DBZ-loaded PLGA microspheres into mouse inguinal white adipose tissue (WAT) depots resulted in browning in vivo. Our results provide the encouraging proof-of-principle evidence for the application of biodegradable polymers as a controlled release platform for delivery of browning factors, and pave the way for development of new translational therapeutic strategies for treatment of obesity.